Valuation of agrifood SMEs. Lessons to be learnt from the stock market - Raül Vidal; Javier Ribal (Spanish Journal of Agricultural Research, 2018)
The European agrifood industry is mostly characterized by small and medium enterprises (SMEs); as in 2013, SMEs represented 99.13% of the total number of companies. The valuation of SMEs not listed in any stock market is a complex task since there is not enough information on comparable transactions. When applying discounted cash flow (DCF) models to value private agrifood companies, the capital structure and the cost of equity are two key parameters to be determined. The implications of these parameters in the value of the enterprise are not clear inasmuch as it is not possible to carry out a contrast due, precisely, to the lack of comparables. The main goal of this study is to determine the biases that those two parameters can introduce into the valuation process of an agrifood company. We have used the stock market as a framework wherein to apply a simple fundamental model to the companies of the European food industry in order to obtain three valuation multiples. By means of two bootstrap approaches, the bias induced in the multiples has been assessed for every year from 2002-2013. Results show that the use of the return on equity as cost of equity tends to undervaluation; the use of capital asset pricing model (CAPM) tends to a slight overvaluation, whereas using the total beta induces an undervaluation bias. Moreover, the capital structure shows little influence on the valuation multiples. The conclusions drawn from this paper can be useful for managers and shareholders of privately-held agrifood companies.